Global regularity of the two-dimensional Boussinesq equations without diffusivity in bounded domains. (October 2018) - Zhou, Daoguo
Abstract: We address the well-posedness for the two-dimensional Boussinesq equations with zero diffusivity in bounded domains. We prove global in time regularity for rough initial data: the initial velocity has ϵ fractional derivatives in L q and the initial temperature is in L q, for some q > 2 and ϵ > 0 arbitrarily small.